PENILAIAN PETANI TERHADAP SIARAN PEDESAAN RADIO PRODAMA (Program Desa Maju) SEBAGAi SUMBER INFORMASI PERTANIAN DI KECAMATAN DUKUN KABUPATEN MAGELANG - Nurul Farida; Totok Mardikanto; Suminah Suminah (AGRITEXTS: Journal of Agricultural Extension, 2005)
Agricultural development in rural areas can be supported by the spread of information through rural broadcasting. Rural broadcasting is aim at spreading th agricultural information toward farmers and their families. Farmer's valuation to rural broadcasting of Radio Prodama as agricultural information resources will affect the continuity of that broadcasting programme. The farmers' appraisal can be affected by their characteristics, while ,heir appraisal includes the judgement toward radio broadcasting programme, the quality and the benefits of rural broadcasting of Radio Prodama as agricultural information resources. This research is aimed at knowing what and how rural broadcasting ofRadio Prodama, study farmer's characteristic correlates to valuation, study farmer's valuatio, study correlation between farmer 's characteristic and farmer's valuation to rural broadcasting of Radio Prodama as agricultural information resources. The basic method used in this research was descriptive methode with survey technique. The location of this research was determined intentionally (purposive), that was, Dulam Subdistrict, Magelang Regency by the consideration of Prodama Radio 's location at Dukun Subdistric. Sampels were taken by using multistage cluster random sampling, as many as 44 respondents. In order to know then used Rank Spearman correlation test by using SPSS 10. 0 for windows to know the correlation between the farmers' characteristics and their valuation ofrural broadcasting ofRadio Prodama as agricultural information resources, where as significance test usingt test. The result of the research showed that realization rural broadcasting of Radio Prodama realization are devided in two parts "Su/uh Tani" and "Semilir Angin Ndalu ". Farmer's characteristic which correlates to farmer 's valuation enclose formal education on the category of 'quite high ', the outcoming ofon the category of 'barely enough ', the farmland category ranging from 2 stakes < L < 3 stakes ( 2 patok < L < 3 patok) and the cosmopolitan on the category of 'quite high'. Farmer 's valuation to the programme and the benefits of rural broadcasting of Radio Prodama was on the 'good' category, while their appraisal toward the quality of Prodama Radio country broadcasting was of the 'quite good' category. . There was a significant relationship between the farmers ' characteristics and their valuation to the radio broadcasting programme, the quality and the benefits of rural broadcasting of Radio Prodama and rural broadcasting of Radio Prodama as agricultural information resources on the level of trust ranging from 50 percent to 99, 9 percent.